2021
DOI: 10.31246/mjn-2020-0074
|View full text |Cite
|
Sign up to set email alerts
|

Energy and protein intakes are associated with stunting among preschool children in Central Jakarta, Indonesia: a case-control study

Abstract: Introduction: Stunting is a major nutritional problem in Indonesia. The prevalence of stunting in DKI Jakarta province was relatively high at 27.5% in 2013 and 17.7% in 2018. This study aims to describe nutrient intakes of children aged 25-30 months and to determine the proportional differences in nutrient intakes between stunting and normal children in Central Jakarta, Indonesia. Methods: A case-control study with a total sample of 121 children aged 25-30 months was conducted in Gambir and Sawah Besar sub-dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 24 publications
0
14
0
4
Order By: Relevance
“…Macronutrient intakes are important and should be consumed in sufficient quantities every day to prevent stunting. 21 Inadequate energy and protein intake in our population study can be the risk of having stunting on their children. Height among our participants showed that their height was comparable to the highlanders of Papua New Guinea.…”
Section: Discussionmentioning
confidence: 82%
“…Macronutrient intakes are important and should be consumed in sufficient quantities every day to prevent stunting. 21 Inadequate energy and protein intake in our population study can be the risk of having stunting on their children. Height among our participants showed that their height was comparable to the highlanders of Papua New Guinea.…”
Section: Discussionmentioning
confidence: 82%
“…Consumption of food sources of protein is associated with the incidence of stunting. Various studies have shown that stunting events are related to inadequate protein intake [14], [15]. Animal side dishes provide protein with higher bioavailability than plant-based side dishes [16].…”
Section: Discussionmentioning
confidence: 99%
“…( 21) Various treatments provided in the GEN NTB program, that are given to the mother and their newborn until the babies reached 1000 day, are important for personal and social development for the children, and not only intented for the physical and fitness development of the children. (22)(23)(24)(25)(26) A breastfeeding process will assist the formation of neurotransmitters in the form of tryptophan as the raw material for making neurotransmitters such as catecholamines and serotonin for the babies. Both neurotransmitters contribute to the focus of attention and maintain emotions and prosocial behavior in children.…”
Section: Discussionmentioning
confidence: 99%